IMPLEMENTASI KEBIJAKAN PELAYANAN JAMINAN PERSALINAN (JAMPERSAL) DI UPTD PUSKESMAS CIDAHU KABUPATEN KUNINGAN (STUDI KASUS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PELAYANAN JAMPERSAL DI UPTD PUSKESMAS CIDAHU KABUPATEN KUNINGAN) - Maya Nurmasari; Mukarto Siswoyo; Sri Wulandari (Universitas Swadaya Gunung Jati, 2013)
Delivery Assurance (JAMPERSAL) are financial guarantees delivery services that includeprenatal care, delivery assistance, postpartum care, including family planning services afterdelivery and newborn care by health workers in health facilities. The research was carried outand the implementation of policies aimed to describe the service guarantees delivery in healthcenters Cidahu Cidahu Sub District Brass. The background of this research is the number ofpregnant women in health centers Cidahu who do not have health insurance. Economic levelof most pregnant women is still very low and therefore can not pay the cost of delivery andcare of their pregnancy. This study aimed to determine the extent of policy delivery assuranceservices in health centers UPTD Cidahu Cidahu Sub District Brass and what are the barriersthat exist in implementing the policy of service delivery assurance (JAMPERSAL) is. Theresearch method used is descriptive qualitative methods approach, drawing on research sitesin UPTD Cidahu District Health Center Cidahu Kuningan district, while the informants in thisstudy was the chief centers, implementing section Jampersal, midwives, and patientsJampersal. Data collection techniques used are literature study, observation, and in-depthinterviews. Analysis of data is done through data reduction, data display, and verification andconclusion. While testing the validity of the data was done by using triagulasi. The theory ofpolicy implementation that is used is the theory of Edwards III, which consists of four factors:communication, resources, disposition and bureaucratic structure. The results of this researchare still lacking implementation of policy implementation service delivery assurance(Jampersal) in UPTD Cidahu District Health Center Cidahu Kuningan district seen from thefactors of communication, resources, disposition, and a bureaucratic structure.